Dreamcatcher - Kasdan, Lawrence, 1949-; Okun, Charles; Goldman, William, 1931-2018; Freeman, Morgan; Jane, Thomas; Lee, Jason, 1970-; Lewis, Damian, 1971-; Olyphant, Timothy; Sizemore, Tom, 1961-; Wahlberg, Donnie, 1969-; Seale, John, 1942-; Davalos, Raul; et al. (Burbank, CA Warner Home Video, 2003)
Four friends with an unusual power become stranded in a blizzard and are confronted by a deadly alien force. As they try to stop this unparalleled horror, the fate of the world is in their hands.
Special features: Widescreen version presented in a "Letterbox" format -- The original ending and 4 other lifted scenes -- Go behind the goosebumps with the cast and creative personnel in 3 documentaries: DreamWriter, an interview with Stephen King; DreamWeavers, the visual effects of Dreamcatcher; and Dream Makers, a journey through production -- Interactive menus -- Teaser trailer -- Scene access -- Language: English ; French (dubbed in Quebec) -- Subtitles: English, French, Spanish.
Title from disc label.
Based on the book by Stephen King.
Director of photography, John Seale ; editor, Raul Davalos, Carol Littleton ; music, James Newton Howard ; costume design, Molly Maginnis ; production design, John Hutman.
Morgan Freeman, Thomas Jane, Jason Lee, Damian Lewis, Timothy Olyphant, Tom Sizemore, Donnie Wahlberg.
MPAA rating: R.
DVD, Region 1 encoding, Dolby digital surround.
Keywords: Human-alien encounters -- Maine -- Drama; Horror films; Feature films; Maine; Drama; Feature films; Video recordings for the hearing impaired; DVDs for the hearing impaired; DVD-Video discs; Suspense